Analisis Efektivitas Mesin AccurioPress 6100 dalam Produksi Cetak Digital Menggunakan Metode OEE - Tentasanu Ilham Berdotu; Rachmah Nanda Kartika; Hibertus Rudi Kusmantoro (Pusat riset dan Inovasi Nasional, 2025)
The development of digital printing technology requires machines with high reliability and efficiency. The AccurioPress 6100 is a widely used digital printing machine that offers a speed of up to 100 pages per minute. However, the machine’s Overall Equipment Effectiveness (OEE) at PT. OctoPrint only ranged from 45% to 53%, which is below the industry standard of 85%. This study identifies the gap in machine efficiency and proposes solutions based on OEE analysis involving Availability, Performance, and Quality indicators. The study adopts a descriptive quantitative method, collecting data through direct observation and interviews over a 14-week period. Preventive maintenance strategies were implemented to improve machine performance. The results showed an increase in OEE to 60–63%, supported by improvements in Mean Time To Failure (MTTF) and reductions in Mean Time To Repair (MTTR).